Imaging, Histopathologic, and Treatment Nuances of Pulmonary Carcinosarcoma - Tyler Gleason; Michael Haas; Brian H. Le (Case Reports in Radiology)
A 76-year-old female with coronary artery disease, chronic obstructive pulmonary disease, diabetes mellitus type II, and 40 pack-year smoking history presented with a four-day history of cough, productive of green-yellow sputum. Chest X-ray revealed opacification of the left upper lung field, and computed tomography (CT) of the chest showed a large cavitary lesion invading the T2-T3 vertebral bodies, extending into the epidural space, giving rise to mild cord compression. Biopsy of the lesion revealed a poorly differentiated neoplasm composed of distinct epithelial and mesenchymal components, consistent with carcinosarcoma. A metastatic workup was negative. Primary lung carcinosarcoma is a rare tumour that can demonstrate an especially aggressive clinical course; diagnosis is often nuanced by limited sampling at initial presentation, especially in a setting of advanced disease and debility that precludes consideration for upfront resection or more extensive, invasive sampling.